Analysis Of The Influence Of Financial Rewards, Motivation, Job Market On Career Intention As A Public Accountant - Heru Sutapa; Dyah Palupiningtyas; Suriadi; Musran Munizu; Masradin (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study intends to examine the idea that financial incentives, labor market factors, and motivation affect students' interest in becoming public accountants. 100 students at one of private university in Indonesia were given questionnaires, which helped collect the study's data. The convenience sampling approach was used to choose the study's sample. Multiple linear regression techniques were used to examine the data using SPSS software. The findings of this study suggest that while labor market factors have a detrimental impact on accounting students' interest in becoming public accountants, motivation has a favorable affect on this desire. Although financial incentives encourage accounting students to choose a career as a public accountant.